Native and Engineered Extracellular Vesicles for the Treatment of Acute Lung Injury and Acute Respiratory Distress Syndrome - Zhengyan Gu; Wenjun Xue; Guanchao Mao; Zhipeng Pei; Jingjing Li; Mingxue Sun; Xinkang Zhang; Shanshan Zhang; Songling Li; Jinfeng Cen; Kai Xiao; Ying Lu; et al. (Small Science)
Extracellular vesicles (EVs) are lipid bilayer nanoparticles naturally released from cells, playing a crucial role in intercellular communication. They modulate gene expression and regulate physiological and pathological processes, including acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Research has shown that EVs contain a variety of active components, are biocompatible and small in size, and do not trigger immune rejection, making the infusion of exogenous EVs a promising therapeutic tool. With further research, engineering strategies have been proposed to enhance the clinical potential of EVs. These strategies involve modifying either donor cells that secrete EVs or the EVs themselves and can be engineered to circumvent the limitations of native EVs. In this review, an overview of the biological properties of native EVs is provided and the current therapeutic potential of native and engineered EVs in treating ALI/ARDS, along with the latest research findings, is summarized. The challenges and opportunities for clinical translation of EVs as a novel therapeutic tool are also discussed, offering new insights into the treatment of ALI/ARDS using EV engineering technology.